Metacognitive Skills Profiles of Students in Solving Higher-Order Differential Equation Problems: A Qualitative Case Study - Asmaun, Asmaun; Liani, Ahyani Mirah (Cita konsultindo, 2026)
Metacognitive skills is essential for solving complex mathematical problems, particularly in higher-order ordinary differential equations that require structured reasoning and reflection. This study aimed to describe university students’ metacognitive skilss profiles in solving higher-order differential equation problems based on their mathematical ability levels. A qualitative case study approach was employed. The population consisted of 43 students from Universitas Negeri Makassar who had enrolled in the Ordinary Differential Equations course. Three students were purposively selected to represent high, moderate, and low mathematical ability levels. Data were collected through problem-solving tests and semi-structured interviews. The data were analyzed qualitatively using the stages of data collection, data reduction, data display, and conclusion drawing, guided by three metacognitive indicators: planning, monitoring, and evaluation. The results showed that students with high mathematical ability demonstrated strong metacognitive awareness by effectively planning, monitoring, and evaluating their problem-solving processes. Students with moderate mathematical ability were able to plan and monitoting their solutions but experienced difficulties in evaluating their work. In contrast, Students with low mathematical ability can maximally fulfill one metacognitive indicator; Planning indicators. Students make a calculation error in the strategy that has been designed so it results in the final result of the answer. These findings highlight the need for instructional strategies that explicitly foster metacognitive awareness to support students in solving advanced differential equation problems.